Product Value Creation Training Through Value Proposition Canvas (VPC) with the South Jakarta Small Medium Enterprise (SME) Community - Ahmad Azmy; Iyus Wiadi; Handi Risza (Jurnal Pengabdian Pada Masyarakat, 2023)
Product value creation training is a community service activity carried out by the Faculty of Economics and Business, Paramadina University. The aim of this program is to increase knowledge and practice of creating product value for MSME actors. The training participants were the South Jakarta MSME Community. The themes presented were digital entrepreneurship, the urgency of product value, and product value mapping with the Value Proposition Canvas. The number of participants was 38 people. The evaluation results showed that the participants were satisfied with this training program. The three aspects assessed are the committee, materials, and the implementation of the concept of product value. The training method is carried out face-to-face by inviting small-medium enterprise community actors in the South Jakarta area. The evaluation questionnaire was distributed online using the Google Form. The results of the evaluation assessment show that the program was successfully implemented with material in accordance with business needs. Training participants have a strong desire to apply the Value Proposition Canvas (VPC) concept to products or services. These This awareness is to be able to meet consumer expectations. The follow-up program will be carried out with the theme of packaging and product branding. These two themes are a continuation of the community service program in the coming year.